An oral cavity profile in illicit- Drug abusers? - Muhammad Mahmoud Al Bush (Wolters Kluwer Medknow Publications, 2019)
Background: The aim of this study is to shed the light on the oral cavity profile assessing teeth and periodontal tissues in previously illicit drug abusers of cannabis and heroin with different drug addiction circumstances. Materials and Methods: Study population included 100 inmates, aged 21-64 years, incarcerated for previous addiction to cannabis or heroin. Personal information and drug circumstances of addiction were registered with dental and periodontal parameters including daily teeth brushing frequency, decayed missed filled teeth (DMFT), plaque index (PI), gingival index (GI), bleeding on probing (BOP), recession, and clinical attachment loss (CAL). Results: Half of the population were illiterate, and 70% were married. Heroin was the most previously abused drug and more than 70% of the participants had been addicted for more than 12 months. Low teeth brushing activity profile dominated with higher values for DMFT and BOP in the heroin group compared with the cannabis (after age adjustment) (DMFT = 22.6 ± 7.9, 18.5 ± 9.8, respectively, P = 0.03) (BOP = 60% ± 30%, 66.6% ± 32%, respectively). In addition, higher values of BOP were recorded in the heroin injecting group compared with both of heroin fumes inhalation and cannabis smoking (BOP = 76.41% ± 27.7%, 59.12% ± 33.6%, 60.05% ± 31.8% P = 0.04, respectively), whereas PI, GI, Reces, and CAL means were comparable among groups regardless of other addiction circumstances. Conclusion: Abused drug type and the way its chemical form being administered would negatively affect, directly or indirectly, the oral cavity concomitantly with the sustained state of self-negligence and less interest in implementing the oral hygiene measurements. Altogether, addiction circumstances synergize leading to a distinctive dental and oral profile which would impose a burden to adapt a more customized treatment approach.